Successful Bailout of Catheter-Induced Dissection in Acute Myocardial Infarction Resulting From a Nondominant Right Coronary Artery Occlusion - Hiroshi Abe; Tadao Aikawa; Ken Yokoyama; Tohru Minamino (Case Reports in Cardiology)
A 48-year-old male with a history of hyperlipidemia presented to the emergency department with chest pain. Electrocardiographic abnormalities indicated an acute coronary syndrome. Urgent coronary angiography revealed nondominant right coronary artery (RCA) occlusion. During primary percutaneous coronary intervention (PCI), a 0.014-inch floppy guidewire could not be easily advanced into the middle RCA due to poor backup support from the guiding catheter and the patient’s breathing. The pressure was monitored several times after reinserting the guiding catheter. Nevertheless, the guidewire was inadvertently inserted into the false lumen from the ostium, leading to subsequent dissection during contrast injection. Intravascular ultrasound (IVUS) imaging confirmed dissection from the ostium to the middle RCA and passage of the guidewire into the false lumen. An additional guidewire was successfully inserted into the true lumen of the RCA using real-time IVUS-guided wiring. We demonstrated successful bailout stenting for catheter-induced dissection of the nondominant small RCA. Our case highlights the risk of coronary artery dissection associated with guiding catheter use, especially in a nondominant small RCA, and the importance of optimal guiding catheter selection for primary PCI. The real-time IVUS-guided wiring technique can be applied to a single 6-Fr guiding catheter and is useful for quickly inserting a guidewire into the true lumen.